Association of the Cardioankle Vascular Index and Ankle-Brachial Index with Carotid Artery Intima Media Thickness in Hemodialysis Patients. (24th June 2013) - Gohda, Tomohito; Gotoh, Hiromichi; Gotoh, Yoshikazu; Yamaguchi, Saori; Tomino, Yasuhiko
Abstract : The objectives of the present study are (1) to compare the cardioankle vascular index (CAVI), ankle-brachial index (ABI), and carotid artery intima-media thickness (CA-IMT) between HD patients with and without type 2 diabetes (T2D) or prevalence of cardiovascular (CV) disease and (2) also to evaluate the relationship of these indices with CA-IMT in these patients according to ABI levels. This study consisted of 132 HD patients with T2D and the same number of patients without T2D. The patients with diabetes or prevalence of CV disease had significantly higher CA-IMT and lower ABI values than those without diabetes or prevalence of CV disease, respectively. Although diabetic patients had higher CAVI than those without diabetes, CAVI did not differ between patients with or without prevalence of CV disease. In univariate analysis, CA-IMT was more strongly correlated with ABI than CAVI. However, the opposite was true in patients with an ABI value of more than 0.95. Both indices were significantly correlated with CA-IMT although ABI was a powerful determinant than CAVI. It appears that both indices are associated with CA-IMT in HD patients, especially with an ABI value of more than 0.95.